Prognostic assessment following acute myocarditis requires convalescent scanning: neither peak troponin nor index scan T2 signal predicts convalescent late gadolinium enhancement. (13th July 2021) - Zaman, S; Vimalesvaran, K; Johns, I; Howard, JP; Cole, GD
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiovascular magnetic resonance (CMR) is a key diagnostic investigation in acute myocarditis (1) and permits quantification of late gadolinium enhancement (LGE) and myocardial oedema.  Follow-up CMR imaging is recommended to check for persistence of scar and oedema (2).  Persistent late gadolinium enhancement is associated with a worse prognosis (3). It is not known whether all patients require follow-up scanning or whether the initial scan can provide useful information to identify which patients need convalescent assessment.  Purpose: In this study we considered whether extent of troponin elevation, extent of T2 elevation and initial late gadolinium enhancement burden predicted long-term late gadolinium enhancement at follow-up. Methods: Index and follow-up CMR scans of consecutive patients presenting with a diagnosis of acute myocarditis between 2019 and 2020 across three hospitals were included. Inclusion criteria were: follow-up scan within 9 months of the index scan, CMR with LGE imaging and T2 mapping, and acute myocarditis being the primary diagnosis of the index scan. Myocardial T2 values in the area affected by myocarditis and percentage of LV myocardium showing late enhancement (using a threshold-based full height half width or manual region of interest strategy) were extracted. Results: 20 patients were included in the study (80% male; mean age 37 years). Mean interval between the index and follow-up scan was 4.1 months.  Peak troponin level during the acute illness was not associated with the proportion of LV myocardium affected by LGE in the index scan (R^2 <0.01) (Figure 1A). Myocardial T2 values in the first scan were not associated with the proportional resolution in LGE between the index and follow-up scans (R^2 0.02) (Figure 1B). The mean change in LGE was -61.7% (+/-22.8%) but the initial LGE burden did not predict the proportional degree of improvement in LGE between scans (R^2 <0.01)(Figure 1C). Conclusions: The extent of troponin elevation and initial CMR phenotype was not a good predictor of the burden of long-term late gadolinium enhancement.  Although most cases showed improvement in LGE scar burden between index and follow-up imaging, neither peak troponin level during the acute episode, nor T2 values at the first CMR scan were predictive of initial or change in scar burden. Serial CMR assessment is required to identify those patients who have residual long-term scarring.